Oegye + in = Alienoid [videorecording (DVD)] - Choi, Dong-hoon; Yi, Ki-ch'ŏl (Screenwriter); Yu, Chun-yŏl, 1986-; Kim, U-bin, 1989-; Kim, T'ae-ri, 1990- (Well Go USA, 2022)
For ages, aliens have kept their prisoners locked inside human bodies, but the guard in charge opens a gate through time in an attempt to prevent their escape. The portal links to 630 years in the past, when a master swordsman and others try to seize a legendary sword. Chaos and confusion ensue when travelers from the present cross paths with those from the past, and all are trying to find the mystical divine blade that holds the key to everything.